Analisis Kelayakan Pengembangan Produk Alat Permainan Edukatif dengan Pengenalan Bahasa Arab bagi Anak Usia Dini - H. Ekie Gilang Permata; Anisa Laila (Jurnal Rekayasa Sistem Industri, 2019)
The Educational Game Tool is a game tool that intentionally designed specifically for educational purposes. In the industrial world, doing business in the world of toys is a very prospect and opportunity. Feasibility studies need to be carried out to avoid risk of loss, facilitate planning, facilitate the implementation of work, facilitate supervision and facilitate control. Consideration is carried out on the technical, financial and market aspects and marketing aspects to see whether these children's toys are feasible or not to be produced and marketed. The purpose of the study was to determine the level of feasibility of developing educational game products by introducing Arabic to early childhood in terms of technical, financial, market and marketing aspects. From the results of the study obtained the level of agreement on the market and marketing aspects of the 15 statements given were above 90.29% which means the statements given by each respondent, the respondents agreed. In technical aspect, it is known that balsa wood has a lead time of one week, so the company must do planning and scheduling orders to do safety stock. In the financial aspects, the initial investment needs of Rp. 166,536,000.00, the NPV has a positive value of Rp. 824,715,456.00 with an interest rate of 8%, the IRR is 67% greater than MAAR 8% and PP is obtained for 1 year 7 months 6 days.